PREDIKSI KONSUMSI BAHAN BAKAR MINYAK UNTUK KENDARAAN DARAT JALAN RAYA SAMPAI TAHUN 2040 MENGGUNAKAN SOFTWARE LEAP - Muhammad Fauzi Aditya Nasri; MSK. Tony Suryo Utomo (JURNAL TEKNIK MESIN, 2015)
This study is designed to predict the fuel consumption for passenger cars, motorcycles, buses and trucks in Indonesia from 2010 to 2040 using LEAP software with two scenarios, as which is business as usual (BAU) by assuming growth of fuel consumption without changes from policies and technologies sector and advanced fuel economy (AFE) assuming an increase in vehicle technology which can affect fuel consumption. The simulation results shows fuel required  for passenger car type vehicle in 2040 based on the BAU is 2,579.6 million gigajoules and 2,229.9 million gigajoules for AFE or savings up to 13.56%. Fuel required for motorcycles in 2040 based on the BAU is 1.792,8 million gigajoules and 1.559,9 million gigajoules based on AFE in 2040 or savings up to 13%. Fuel required bus type vehicle in 2040 based on the BAU is 689,6 million gigajoules and 621,9 million based on AFE or fuel savings up to 9,82% . Fuel required for truck type vehicle based on the BAU in 2040 is 4.598,2 million gigajoules and 3,983.0 million gigajoules based on AFE or savings up to 13.39 %.  Exhaust emissions produced by vehicles are passenger cars, motorcycles, buses and trucks in 2040 for the BAU is Carbon Dioxide Non Biogenic (CO2) 266,4 billion Metric Tonnes, Carbon Monoxide (CO) 56,7 billion Metric Tonnes and Nitrogen Oxides (NOx) 31,1 billion Metric Tonnes. As for the AFE, in 2040 for CO2 230,7 billion Metric Tonnes, CO 56,7 billion Metric Tonnes and NOx 31.1 billion Metric Tonnes. At year 2040 the value of CO2 on AFE scenario decreased by 13,41% compare to BAU scenario, but the value of  NOx and CO in the AFE and the BAU scenario is same.